(untitled) (European Journal of Education and Psychology, 2008)
The aim of this study is to supply information on the effects of strategic training in the area of mathematics (1) on the real level, as well as the perceived competence in terms of the skills the students show to select, organise and produce information and (2) their attitude and motivation towards working in this area of the curriculum. 104 students took part in this study, 57 of whom where the control group and 47 the experimental one. The teachers and students who took part in this experience followed an on-line course to handle the “hypertext” strategy for three months, approximately. The results show that the strategic training implemented in this study highly improves the written understanding procedures, increases the perceived competence for internal information handling and generates positive changes in terms of attitude and motivation of the students towards working in the area of mathematics. Key words: Mathematics, primary education, strategic training.